Effect of Gibberlic acid and Glycine on shoots length and callus weight for three cultivars of Date palm propagate in vitro - Laith. A. Hatem; Attaalah. I. Alwan; mohammed. k. Hamed; Ghania. H. Fathel; Hamza. A. Ibraheem (Journal of Madenat Alelem University College, 2011)
The study was conducted to test the effect of different concentration of GA3 (0, 0 , 0.2 ,0.3, 0.4) mg/L and Glycine (0, 3, 5) mg/L on shoots length and callus weight in depended experiments for three cultivars of Date Palm ( Kharowi, Maktoom and Tebarzal ) which propagated in vitro . The results showed that using high concentration of GA3 increased shoot length in all cultivars. The concentrate 0.4 mg/L and cultivar Tebarzal were superior to gave shoot length reached 2.98 cm and 2.52 cm, respectively. The results showed that add Glycine on medium not gave significant effect on callus weight as compared with control.